The current role of circulating biomarkers in non-muscle invasive bladder cancer - Rink, Michael; Schwarzenbach, Heidi; Vetterlein, Malte W.; Riethdorf, Sabine; Soave, Armin (Translational Andrology and Urology; Vol 8, No 1 (February 28, 2019): Translational Andrology and Urology (Management of Non-muscle Invasive Bladder Cancer), 2018)
Non-muscle invasive bladder cancer (NMIBC) is characterized by its high rate of disease recurrence and relevant disease progression rates. Up to today clinical models are insufficiently predicting outcomes for reliable patient counseling and treatment decision-making. This particularly is a serious problem in patients with high-risk NMIBC who are at high risk for failure of local treatment and thus candidates for early radical cystectomy or even systemic (neoadjuvant) chemotherapy. Next to its clinical variability, bladder cancer is genetically a highly heterogeneous disease. There is an essential need of biomarkers for improving clinical staging, real-time monitoring of disease with or without active treatment, as well as improved outcome prognostication. Liquid biopsies of circulating biomarkers in the blood and urine are promising non-invasive diagnostics that hold the potential facilitating these needs. In this review we report the latest data and evidence on cell-free circulating tumor desoxyribonucleic acid (ctDNA) and circulating tumor cells (CTC) in NMIBC. We summarize their current status in clinical diagnostics, discuss limitations and address future needs.